Fatores de risco e proteção: saúde mental de mães e filhos, suporte social e estilo parental - Cid, Maria Fernanda Barboza (2008)
Studies indicate that some family characteristics, such as poverty and parents’ low education, low levels of social support, high levels of marital discord, parents’ depression and parents’ mental disorders are risk factors that influence children development. It is observed that among those characteristics, the parents’ mental disorder has been considered a relevant vulnerability factor influencing children’s development. Some studies indicate that mothers who suffer from mental disorders are less affectionate to their children, less available to their needs and demonstrate high levels of insecurity and anxiety. The purposes of this study were: identifying the parenting and the social support levels of mothers who suffer from humor disorders and investigating the relation between these elements and the social-emotional development levels of their children. The participants were ten children aged between 7 and 12 years old and their mothers: five children of mothers with mental disorders and five children of mothers without mental disorders, who composed the control group. The instruments which were used in the data collect were: Strengths and Difficulties Questionnaire (SDQ), which evaluated the children’s socialemotional development; Parenting Style Inventory (IEP), that aimed to identify the mothers’ parenting in their children’s education and the Social Support Questionnaire (SSQ), which evaluated the social support provided to the mothers. The data analyses were carried out through statistic studies. The results indicate that the mothers who suffer from humor disorders are less satisfied with the social support that is provided to them. Also, they punish their children in a less consistent way when compared with mothers from the control group. Moreover, it was identified in mothers with mental disorders a risky parenting that can contribute to the development of anti-social behaviors in their children. Concerning the children’s social-emotional development, the results did not reveal significant differences between the groups, so that the maternal humor disorders do not seem to influence directly the children’s social-emotional development.